Offshore Wind Farm Footprint on Organic and Mineral Particle Flux to the Bottom - Ivanov, Evgeny; Capet, Arthur; De Borger, Emil; Degraer, Steven; Delhez, Eric J. M.; Soetaert, Karline; Vanaverbeke, Jan; Grégoire, Marilaure (Frontiers in Marine Science, 2021)
Offshore wind farms (OWFs) are an important source of renewable energy accounting for 2.3% of the European Union's electricity demand. Yet their impact on the environment needs to be assessed. Here, we couple a hydrodynamic (including tides and waves) and sediment transport model with a description of the organic carbon and mineral particle dynamics in the water column and sediments. The model is applied to the Belgian Coastal Zone (BCZ) where OWFs currently occupy 7% of its surface area which is estimated to double in the next 5 years. The impact of OWFs on the environment is represented through the filtration of the water column and faecal pellets production by the blue mussel, the dominant fouling organism. Model simulations show that the impact of biodeposition on the mud particle sedimentation and on sediment composition is small compared to the fluxes associated with tidal deposition and resuspension and the lateral inputs In contrast, the total organic carbon (TOC) flux to the sediment is significantly altered and TOC deposition is increased up to 50% in an area 5 km around the monopiles. Further away, the TOC flux to the bottom decreases with a notable effect up to 30 km away. The major changes are found along the direction of the main residual current and tidal ellipse's major axis. In addition, sub-mesoscale gyres act as retention areas with increased carbon deposition. A future OWF in the BCZ will be located close to gravel beds in a Natura 2000 area, considered as vulnerable habitats and biodiversity hotspots. Different scenarios for this OWF, varying in turbine number and positioning, are compared in terms of impact on the carbon and mineral particle deposition flux in the BCZ and, particularly, to these gravel beds. The scenarios show that the number of turbines has only a slight impact on the TOC deposition flux, unlike their positioning that significantly alters the TOC flux to the gravel beds. The TOC deposition flux exceeds 50%, when the turbines are placed next to the gravel beds; while a limited increase is simulated, when the turbines are located the farthest possible from them.